RelAte: pilot study of the effects of a mealtime intervention on social cognitive factors and energy intake among older adults living alone. Issue 9 (28th October 2016) - McHugh Power, Joanna E.; Lee, Olga; Aspell, Niamh; McCormack, Emma; Loftus, Michelle; Connolly, Leona; Lawlor, Brian; Brennan, Sabina
Abstract: Mealtime interventions typically focus on institutionalised older adults, but we wanted to investigate whether they may also be effective among those living independently. Using a randomised controlled trial design, we assessed the effects of a novel mealtime intervention on self-efficacy, food enjoyment and energy intake. A total of 100 adults living alone aged over 60 years were randomised to the treatment or control conditions: all received a guidebook on nutrition and culinary skills. Treatment group participants received a weekly visit from a trained volunteer who prepared and shared a meal with them. Participants in the treatment group showed improvements relative to those in the control group at borderline significance ( P =0·054) for self-efficacy and at significance for food enjoyment. Significant improvements were observed in female participants in the treatment but not in the control group in energy intake (although following corrections for multiple comparisons, only the effect on food enjoyment remained significant). These findings will inform the design of future complex interventions. For this type of intervention to be successful, more focus has to be placed on making interventions more personalised, potentially according to sex. Findings are important for nutritional sciences as they indicate that, in order to improve energy intake and food enjoyment among older adults, multimodal nutritional interventions including social components may be successful.